Synthesis of Al-Y doped-lithium lanthanum zirconate and the effect of cold isostatic pressure to its electrical properties - Fitria Rahmawati; Septia K Arifah; Yuniawan Hidayat (International Journal of Renewable Energy Development, 2023)
This research aims to study the Al-Y dopant to Lithium Lanthanum Zirconate (LLZO) to the characteristics and electrical properties of the LLZO as solid electrolyte. The synthesis was conducted through solid state reaction with Al2O3 and Y2O3 as dopant precursors. X-ray diffraction analysis along with Le Bail refinement was done to understand their structure, and phase content inside. The result found that Al and Y doping increased the cubic phase from 49.58% to 84.91%. The Al-Y doped-LLZO (LLZAYO) powder was then treated by a various cold isostatic pressing, CIP of 0, 20, 30, and 40 MPa to understand the effect of cold isostatic pressure to the ionic conductivity and solid electrolyte performance of the material even without heat sintering treatment. The result found that the green pellet of LLZAYO) which was isostatically pressed by 40 MPa at room temperature provides (9.06 ±0.26) x10-6 Scm-1, about 8 times higher than the LLZO without doping, i.e., (1.25 ±0.01) x 10-6 Scm-1. All solid-state battery with the prepare LLZAYO CIP 40 as solid electrolyte shows reversible reaction of Li/Li+ redox accompanied with Al/Al3+ redox. The Al/Al3+ reaction seems to decrease the electronic resistance between LCO-LLZAYO CIP40-Li which causes the full cell performance to decrease. The initial specific charging capacity is 82 mAh/g, and the initial discharge was 83 mAh/g, confirming 101 % of Coulombic efficiency. The discharge capacity drops to 46 mAh/g at second cycle, leading to a decrease in Coulombic efficiency to 56 %.